THE IMPLEMENTATION AND EFFECTIVENESS OF INTEGRATED APPROACHES IN IMPROVING ENGLISH BASIC SKILLS FOR BEGINNERS - Jaka Satria Warman; Fika Mardiyah (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2019)
There are a lot of approaches in learning a new language particularly English and there have been many studies that attempted to seek the best one. However, the attempts have failed because there is no single approach that can be considered as the best one. That is because each approach has its own advantages and drawbacks and most of them are situational. Therefore, this study combined some of the approaches in order to create a more effective language teaching method. The main objectives of this study were 1) to see the applicability of the implementation of the integrated approaches and 2) to find out the effectiveness of the implementation of the integrated approaches in improving English basic skills for beginners. Action research design as well as quantitative analysis by using statistical calculation ware used in this study as the research method. The result of this study showed that there were two main obstacles in implementing the integrated approaches and there was a significant positive impact of using the integrated approaches in improving the beginners’ English basic skills.